Cobalt(ii) 8-hydroxyquinoline complexes: structure, cytotoxicity and action mechanism12. Issue 5 (21st April 2016) - Zhang, Hai-Rong; Huang, Ke-Bin; Chen, Zhen-Feng; Liu, Yan-Cheng; Liu, You-Nian; Meng, Ting; Qin, Qi-Pin; Zou, Bi-Qun; Liang, Hong
Abstract : Three cobalt(ii ) complexes with 8-hydroxyquinoline derivatives as ligands were synthesized. They exhibited strong proliferation inhibition activity against T-24 cancer cells, which induced cancer cell apoptosis via intrinsic caspase-mitochondria pathways. Abstract : Three cobalt(ii ) complexes, [Co(NOQ)2 (C5 H5 N)2 ]C2 H5 OH (1 ), [Co(BrQ)2 (C5 H5 N)2 ] (2 ) and [Co(NQ)2 (C5 H5 N)2 ] (3 ) (NOQ = 5-nitro-8-hydroxyquinoline, BrQ = 5-bromo-8-hydroxyquinoline, NHQ = 2-amino-8-hydroxyquinoline), were synthesized and characterized. Their in vitro cytotoxicity against T-24, BEL-7404, HepG2, HeLa, MGC-803, SKOV-3, HL-7702 and WI-38 cell lines was evaluated. Complexes1–3 exhibited the highest proliferation inhibition activity against the T-24 tumor cell line with IC50 values in the range between 7.00 and 16.70 μM. They also displayed selectivity towards T-24 tumor cell lines compared to the normal liver cell line HL-7702 and human fetal lung fibroblast WI-38 cell line. The action mechanism of complex 1 was investigated. It caused apoptotic death of the T-24 cells via G1 cell cycle arrest. Further investigation revealed that complex1 induced overproduction of reactive oxygen species, which led to mitochondrion-mediated apoptosis. DNA binding studies suggested that intercalation might be the most probable binding mode of the Co(ii ) complexes with ct-DNA.